Control of tomato early blight and wilt using aqueous extract of neem leaves - HASSANEIN, Naziha M.; ALI, Mohammed; YOUSSEF, Khayria A.; MAHMOUD, Dalia A. (Phytopathologia Mediterranea, 2010)
The effect of neem (Azadiracta indica) leaf extract against Alternaria solani and Fusarium oxysporum, the causal agents of early blight and wilt of tomato plants (Lycopersicon esculentum Mill.) respectively, was studied. Concentrations (5, 10 and 20%) of aqueous neem extract suppressed mycelial growth of both pathogenic fungi and the degree of suppression gradually increased with increasing concentration. A concentration of 20% aqueous neem leaf extract sprayed on tomato plants lowered the incidence of Alternaria early blight from 53.2 to 42.5% after two weeks and from 100 to 79.2% after 4 weeks. Spraying plus irrigation with the same extract lowered the severity of Alternaria early blight from 26.8 to 11.4% after 2 weeks and from 61.7 to 17.9% after 4 weeks (control ratio of 43.71% after 4 weeks). For F. oxysporum wilt, germination of tomato seeds was highest in pots containing the negative control (soil free of pathogen) and in pots irrigated with the aqueous neem extract. The lowest disease incidence (19.04%) was obtained in pots treated with the pathogen and irrigated with aqueous neem extract, where an 81% control of Fusarium wilt was achieved. Growth parameters of tomato (shoot and root length, number of leaves, fresh and dry weight of shoots and roots) were studied 4, 6 and 8 weeks after sowing in the presence of the pathogens. There was a significant gradual increase in growth parameters when the plants were sprayed and irrigated with aqueous neem extract with the greatest improvement recorded 8 weeks after sowing.